Digital gap and uses of ICT in a rural school during COVID-19 - Niño Carrasco, Shamaly Alhelí; Parra Encinas, Karla Lariza (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Despite the efforts of past decades, the lack of technological enablement within rural schools in Mexico has been exposed during the closure of schools by Covid-19. An exploratory study was carried out to identify the levels of digital access gap experienced by teachers at an educational center in a rural area of Mexico and to explore the strategies for the use of ICT deployed to ensure academic continuity during the pandemic. It was found that even with limited technological access, various uses of ICT were developed for the development of teaching and learning processes.